'Prosperity a part of the atonement': An interpretation of 2 Corinthians 8:9 - Abiola Mbamalu (Verbum et Ecclesia, 2015)
This article investigates the claim made by some Pentecostal preachers that prosperity is part of the atonement. The biblical basis that such preachers present for their claims is a specific understanding of 2 Corinthians 8:9. The phrase, δια υμας, is sometimes translated for your sakes or because of you, and the verse is understood by these preachers as indicative of the vicarious nature of the poverty of Jesus. A reading of the Greek text of 2 Corinthians 8:9, however, does not lend itself to this interpretation. Furthermore, Pauls act of soliciting for funds to help the poor saints in Jerusalem makes the claim that prosperity is part of the atonement quite unwarranted by the text. Intradisciplinary and interdisciplinary implications: The contextual perspective this work is challenging is the Neo-Pentecostal interpretation of 2 Corinthians 8:9, that prosperity is part of the atonement. This research discountenances such understanding and affirms the traditional view that the scope of the atonement of Christ does not imply financial abundance. The atonement of Christ, however, does have financial implications, for it has brought about a new community that cares for its members.